11 de março de 2004: a imagem fotojornalística do atentado terrorista de Madri - Lucas, Silvana Mendes (2004)
This discourse promotes a study semiotics of the photojournalistic image of the layer of the El periodicals Country, Periodical of Brazil, Leaf of São Paulo and Diário Catarinense, published in the following day to the terrorist attempted against one, occurrence in 11 of March of 2004, the station of Atocha train in Madrid, in Spain. It verifies if the digital technology used na captation, edition and transmission das images brings new understanding, ideology and ethics on the photojournalism in the world contemporary and analyzed the signs comparativily gifts nas photographs, in the perspective semiotics of Charles Peirce and other authors. To add interviews with photojournalists, photograph publishers and publishers daily periodical heads to analyze the manipulation that the digital photograph provides.